Mapping eIF5A binding sites for Dys1 and Lia1: In vivo evidence for regulation of eIF5A hypusination - Thompson, Gloria M. [UNESP]; Cano, Veridiana S.P. [UNESP]; Valentini, Sandro Roberto [UNESP] (Wiley, 2003)
The evolutionarily conserved factor eIF5A is the only protein known to undergo hypusination, a unique posttranslational modification triggered by deoxyhypusine synthase (Dys1). Although eIF5A is essential for cell viability, the function of this putative translation initiation factor is still obscure. To identify eIF5A-binding proteins that could clarify its function, we screened a two-hybrid library and identified two eIF-5A partners in S. cerevisiae: Dys1 and the protein encoded by the gene YJR070C, named Lia1 (Ligand of eIF5A). The interactions were confirmed by GST pulldown. Mapping binding sites for these proteins revealed that both eIF5A domains can bind to Dys1, whereas the C-terminal domain is sufficient to bind Lia1. We demonstrate for the first time in vivo that the N-terminal α-helix of Dys1 can modulate enzyme activity by inhibiting eIF5A interaction. We suggest that this inhibition be abrogated in the cell when hypusinated and functional eIF5A is required. © 2003 Published by Elsevier B.V. on behalf of the Federation of European Biochemical Societies.
Keywords: DYS1; eIF5A; Hypusination; LIA1; Two-hybrid; YJR070C; fungal protein; initiation factor; ligand; protein Dys1; protein eIF5A; protein Lia1; unclassified drug; alpha helix; amino terminal sequence; binding site; cell viability; enzyme activity; enzyme regulation; gene mapping; genetic code; hypusination; nonhuman; priority journal; protein analysis; protein binding; protein domain; protein function; protein interaction; protein modification; protein processing; RNA translation; Saccharomyces cerevisiae; translation initiation; translation regulation; two hybrid system; Binding Sites; DNA, Complementary; Fungal Proteins; Genes, Reporter; Glutathione Transferase; Ligands; Models, Molecular; Oxidoreductases Acting on CH-NH Group Donors; Peptide Initiation Factors; Protein Processing, Post-Translational; Protein Structure, Secondary; Protein Structure, Tertiary; Recombinant Proteins; RNA-Binding Proteins; Two-Hybrid System Techniques